Profil Plumbum (Pb) dan Cadmium (Cd) sebagai Kontaminan Dampak Penggunaan Agrokimia serta Remediasi Biji Kedelai Menggunakan Swelling Agent pada Khelasi dengan Asam Sitrat - Priyadi, Sapto; Darmaji, Purnama; Santoso, Umar; Hastuti, Pudji (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This research were aimed to know the plumbum (Pb) and cadmium (Cd) profile on soybean seeds as contaminants of the impact use of agrochemistry material impact and to know of swelling agent of N,N-dimethylformamide (DMF) needs at certain level of pH in chelation with citric acid. The results showed that the content of Pb in soybean seeds at cultivation system agrochemistry materials i.e. 0.63 ppm, while cultivation system without agrochemistry materials i.e. 0.46 ppm. Cd content in soybean seeds at cultivation system agrochemistry materials i.e. 0.05 ppm and the cultivation system without agrochemistry materials i.e. 0.1 ppm. Acceptable daily intake in terms of Pb content in soybean after treatment increases to 2.93 times compared before treatment (11.3379 to 33.2099 g per body weight per day). Acceptable daily intake in terms of the content of the Cd in soybean after treatment increases to 5.26 times compared before treatment. The value of the bio-concentration factor which expressed an accumulation of Pb in soybean seeds on both cultivation is low system (BCF<250), while for Cd is a moderate to high level (1.000<BCF>250). Cd reduction on soybeans seeds for all chelation treatment was maximum (not detected-detection limits was 0.01 ppm), while the highest reduction of Pb occurs at swelling agent N, N-dimethylformamide 15 mL at pH 10.